Representation of Flowers in the Lyrics of the Songs Bunga Maaf and Bunga Abadi and the Nitizen Comment - Yurnaningsih Guzali; Salam; Yunus Dama (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Song lyrics are not merely a sequence of words to be sung, but texts that convey values, situations, and emotional messages through figurative language such as metaphor, symbolism, hyperbole, and personification. Listeners actively construct meaning based on their experiences, emotions, and backgrounds, making interpretation subjective and personal. Therefore, this study focuses on two songs that feature the flower symbol in their lyrics, namely Bunga Maaf by The Lantis and Bunga Abadi by Rio Clappy, to describe how university students and YouTube netizens interpret the symbolic meaning of flowers within both songs. This study employs the theory of literary pragmatics, which emphasizes the role of the audience as meaning-makers, showing that a song only becomes meaningful when responded to by its listeners. The analysis also incorporates the concept of symbols, the perspective that considers songs as a form of literary work, and emotional classifications reflected in the lyrics to strengthen the interpretation process. The research uses a descriptive qualitative method, with data collected through YouTube comments, semi-structured interviews with students, and note-taking related to statements from the songwriters about the intended meaning of their songs. The findings are presented by linking the interpreted meanings with relevant theoretical frameworks to explain how symbolic representation and emotional elements shape the relationship between the singer, the text, and the audience. The results indicate that in Bunga Maaf, flowers symbolize regret, longing, and the desire to correct past mistakes, while in Bunga Abadi, they represent sincerity and everlasting love. These variations in interpretation highlight the influence of each listener’s emotional involvement and personal experience in constructing meaning.